Infective endocarditis and COVID -19 coinfection: An updated review - George, Anu; Alampoondi Venkataramanan, Sai Vikram; John, Kevin John; Mishra, Ajay Kumar (Acta Biomedica Atenei Parmensis, 2022)
With the rising number of COVID-19 patients, there have been reports of patients presenting with concomitant infective endocarditis. In this retrospective review, we included all articles from Medline with COVID-19 and infective endocarditis coinfection. Ten articles were identified from eight different countries over the world over the past 11 months. All patients reported with the above coinfections were male with a mean age of 53 years. Clinical features of COVID-19 and the presence of ground-glass opacity in CT thorax were predominant among patients with positive RT-PCR for COVID-19. New-onset embolic infarct, pulmonary edema was a contributor to the diagnosis of endocarditis in most patients. Involvement of the aortic valve was most common. Delayed diagnosis and cardiac surgery were contributors to increased morbidity.